2014
DOI: 10.1002/prot.24711
|View full text |Cite
|
Sign up to set email alerts
|

An analysis approach to identify specific functional sites in orthologous proteins using sequence and structural information: Application to neuroserpin reveals regions that differentially regulate inhibitory activity

Abstract: The analysis of sequence conservation is commonly used to predict functionally important sites in proteins. We have developed an approach that first identifies highly conserved sites in a set of orthologous sequences using a weighted substitution-matrix-based conservation score and then filters these conserved sites based on the pattern of conservation present in a wider alignment of sequences from the same family and structural information to identify surface-exposed sites. This allows us to detect specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Neuroserpin was first identified in the secreted product of cultured neuronal axons (Osterwalder et al, 1996). Protein expression is primarily localized to neurons (Osterwalder et al, 1996; Hastings et al, 1997; Lee et al, 2015b). The protein neuroserpin is encoded in mouse and human by the gene Serpini1.…”
Section: Neuroserpin: a Case For A Novel Neuroprotective Treatmentmentioning
confidence: 99%
“…Neuroserpin was first identified in the secreted product of cultured neuronal axons (Osterwalder et al, 1996). Protein expression is primarily localized to neurons (Osterwalder et al, 1996; Hastings et al, 1997; Lee et al, 2015b). The protein neuroserpin is encoded in mouse and human by the gene Serpini1.…”
Section: Neuroserpin: a Case For A Novel Neuroprotective Treatmentmentioning
confidence: 99%
“…An intriguing correlation may be made with recent findings by Lee et al (2015) , who showed that NSP-t-PA complex stability is dependent on evolutionarily conserved residues in NSP, and their findings will inform design of future NSP-mutants to identify the amino acid residues that are ultimately responsible for the pH dependency of NSP-t-PA complex deacylation.…”
Section: Discussionmentioning
confidence: 63%
“…Other results, however, indicate that neuroserpin does not behave as a classical inhibitory serpin toward tPA. Unlike most covalent serpin:protease complexes, tPA:neuroserpin is unstable and dissociates within minutes to release cleaved neuroserpin and active tPA (Barker-Carlson et al, 2002 ; Ricagno et al, 2009 ; Lee et al, 2015 ). As complex dissociation is expected to occur prior to clearance (Barker-Carlson et al, 2002 ), these data suggest that neuroserpin is likely to function as a transient inhibitor of tPA in vivo .…”
Section: Neuroserpin As An Inhibitor Of Tpamentioning
confidence: 99%
“…As complex dissociation is expected to occur prior to clearance (Barker-Carlson et al, 2002 ), these data suggest that neuroserpin is likely to function as a transient inhibitor of tPA in vivo . Interestingly, evolutionarily conserved residues in neuroserpin regulate the half-life of tPA:neuroserpin complexes, suggesting that the precise half-life of the complexes may be physiologically important (Lee et al, 2015 ). tPA:neuroserpin interactions may involve other players, such as an unknown co-factor that stabilizes the complex (Barker-Carlson et al, 2002 ).…”
Section: Neuroserpin As An Inhibitor Of Tpamentioning
confidence: 99%